The concept of a vertical city as an object of designing in conditions of The Sahara desert in the territory of Marzuga, Morocco - Shatrova, I.; Noussair, Amakchi (Ways to Improve Construction Efficiency, 2019)
Analysis of theoretical studies allowed to trace a number of principles of designing a vertical city, as a multifunctional building, in the conditions of the Sahara desert. The concept of Arcology, which is the basis of modern projects of vertical cities, behaves like a living organism, is revealed, reacting to temperature changes and provide energy and nutrition for themselves. The significance of the results of the study is revealed in the development of an architectural solution optimally for construction in the Sahara Desert area (m. Marzuga), and develops the concept of a "vertical city".